Giovanna Motta Baroni in camicia rossa, Passigli, Firenze 2011. ISBN: 978-88-36812-62-2 - Battaglia, Antonello (Mediterranean Journal of Social Sciences, 2011)
Book Review: Giovanna Motta Baroni in camicia rossa, Passigli, Firenze 2011. ISBN: 978-88-36812-62-2